Synergy of Public Policy and Women's Empowerment: Skills Training as a Strategy to Strengthen Family Economy - Afifuddin Afifuddin; Loso Judijanto; Ernawati Ernawati; Rikha Murliasari; Didik Supriyanto (Universitas Teuku Umar, 2026)
This research aims to examine the synergy between public policy and women's empowerment through skills training as a strategy to strengthen the family economy in the ‘Bangga Kencana’ programme in Wonoayu Village, Wajak District, Malang Regency. This research uses a qualitative case study approach, using in-depth interviews, direct observation, and document analysis. Data were analysed using thematic analysis to identify patterns and relationships between policy support and training effectiveness. Coding techniques were applied to categorise key themes relating to skills improvement, economic impact, and program challenges. The results showed that 70% of participants experienced improved skills, and household income increased by 15-25% within six months. However, only 40% received post-training mentoring, limiting the long-term impact. The main challenges faced were limited access to finance (50%), limited market networks (30%), and social norms (20%) that inhibit women's economic participation. While existing public policies aim to support women's empowerment, there are still gaps in implementation, requiring a more integrated approach. This study highlights the importance of integrating policy interventions with local needs by enhancing financial accessibility, expanding market linkages, and ensuring continuous mentoring to sustain empowerment outcomes. The research provides practical policy recommendations to strengthen women’s economic participation, contributing to poverty reduction, gender equality, and sustainable rural development.